2017
DOI: 10.1016/j.ydbio.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Temporal, spatial, and phenotypical changes of PDGFRα expressing fibroblasts during late lung development

Abstract: Many studies have investigated the source and role of epithelial progenitors during lung development; such information is limited for fibroblast populations and their complex role in the developing lung. In this study, we characterized the spatial location, mRNA expression and Immunophenotyping of PDGFRα+ fibroblasts during sacculation and alveolarization. Confocal microscopy identified spatial association of PDGFRα expressing fibroblasts with proximal epithelial cells of the branching bronchioles and the dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 76 publications
6
102
0
Order By: Relevance
“…4J). During alveogenesis, there is normally an increase in Pdgfra + cells (Branchfield et al, 2016;Endale et al, 2017;Gouveia et al, 2017) in the alveolar region, reflecting a necessity for Pdgfra + cells during this stage of development. At P7, Pdgfa fl/− ; Spc-cre; Pdgfra GFP/+ lungs sustained a significant decrease in the expression of Pdgfra GFP -positive cells, compared with control lungs (Fig.…”
Section: Lung Epithelial Deletion Of Pdgfa Results In Developmental Amentioning
confidence: 99%
See 1 more Smart Citation
“…4J). During alveogenesis, there is normally an increase in Pdgfra + cells (Branchfield et al, 2016;Endale et al, 2017;Gouveia et al, 2017) in the alveolar region, reflecting a necessity for Pdgfra + cells during this stage of development. At P7, Pdgfa fl/− ; Spc-cre; Pdgfra GFP/+ lungs sustained a significant decrease in the expression of Pdgfra GFP -positive cells, compared with control lungs (Fig.…”
Section: Lung Epithelial Deletion Of Pdgfa Results In Developmental Amentioning
confidence: 99%
“…They play important roles in development, homeostasis and disease, and downstream signaling from the PDGFRs is known to regulate cell differentiation, proliferation, migration, actin reorganization and apoptosis (reviewed by Andrae et al, 2008). In mice, PDGFRα and PDGF-A are expressed in the lung from embryonic time points to adulthood (Branchfield et al, 2016;Endale et al, 2017;Gouveia et al, 2017;Ntokou et al, 2015). Pioneering studies of global Pdgfa knockout (Pdgfa −/− ) mice demonstrated a role for PDGF-A in lung development.…”
Section: Introductionmentioning
confidence: 99%
“…Mature oligodendrocytes comprise one cluster, having potentially differentiated following initial tamoxifen labeling of PDGFRα expressing progenitor cells. Also captured in the sequencing were three cell-types outside the oligolineage that are known to either express PDGFRα or come from PDGFRα expressing precursors, including fibroblasts, endothelial cells, and 2 populations of pericytes [29][30][31][32] . These clusters were identified by expression of known cell type markers such as Igfbp6 and Fn1 (fibroblasts), Tek, Pecam1, and Kdr (endothelial cells), as well as Rgs5, Pdgfrb, and Des (pericytes) [33][34][35][36] .…”
Section: Profiling the Molecular Signature Of Opcs In The Adult Brainmentioning
confidence: 99%
“…How the ECM deposition is dysregulated in BPD is also a matter of much interest, and this idea is currently being extensively explored in the context of (myo)fibroblast subpopulations in the developing lung, where (myo)fibroblasts may be marked by platelet-derived growth factor receptor (PDGFR)α, or perilipin-2, or combinations thereof. Lineage tracing and other studies have highlighted the likely role of (myo)fibroblast subpopulation in normal and aberrant lung development 155, 156 , and these studies await causal analysis, for example, by in vivo depletion studies. The dysregulation of signaling by the elastogenic growth factor, transforming growth factor (TGF)-β 157 ; and the ability of TGF-β to regulate aberrant alveolarization and ECM production in a BPD animal model 158 underscores a key regulatory role for TGF-β in ECM production and remodeling in the developing lung.…”
Section: Disruption Of Essential Developmental Pathwaysmentioning
confidence: 99%